Productive Capacities Development: Challenges and Opportunities - The Case of Kenya - UN Trade; Development (United Nations, 2025)
The publication consists of two parts. Following the Introduction, which provides the conceptual background and a comprehensive assessment of the recent performance of Kenya’s economy and development, is Part I – the National Productive Capacities Gap Assessment. The NPCGA of Kenya examines the state of the country’s national productive capacities and binding constraints to its structural transformation, economic diversification and overall sustainable development. It uses the Productive Capacities Index (PCI), which relies on eight components – Natural Capital, Human Capital, Transport, Energy, ICT, Institutions, Private Sector and Structural Change – to measure gaps in productive capacities. It then proposes specific, tailored policy interventions to address these challenges. Part II – the Holistic Productive Capacities Development Programme (HPCDP) – provides details on how best to address the gaps and limitations and key binding constraints to the country’s development through a comprehensive programme. The HPCDP is tailored to specific domestic circumstances, comparative advantages, and national institutional frameworks and provides strategic orientation and action-oriented, step-by-step approaches to tackle these key binding constraints. It is designed to address Kenya’s deep-rooted development challenges, as articulated in the NPCGA, by moving away from the practice of short-term, sectoral and fragmented, project-based interventions towards long-term, integrated, and programme-based approaches to development.